2020
DOI: 10.1186/s13104-020-05336-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of Candida species diversity among patients with oral squamous cell carcinoma and oral potentially malignant disorders

Abstract: Objectives To determine the prevalence of Candida species by PCR–RFLP method in the saliva of patients with oral squamous cell carcinoma (OSCC), oral potentially malignant disorders (OPMD) and healthy cohorts. Unstimulated saliva was collected from patients with OSCC (n = 97), OPMD (n = 200), and healthy controls (n = 200). Candida species were isolated using the standard protocol. The isolates were identified using phenotypic and genotypic methods. The odds/risk ratio was calculated using Pearson’s Chi-square… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 17 publications
2
15
0
2
Order By: Relevance
“…Candida spp. were associated with OSCC; increased relative abundances of this fungi were observed in saliva samples from patients with OSCC compared to those taken from healthy individuals and, similarly, in tumoral tissue compared to fibroepithelial polyps [ 82 , 83 ]. A microbial coexistence of C. albicans and a periodontal pathogen P. gingivalis has been described; these two microorganisms have a relationship in which C. albicans shields the P. gingivalis from recognition by the host immune system and, in this way, supports the bacterial infection [ 118 ].…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Candida spp. were associated with OSCC; increased relative abundances of this fungi were observed in saliva samples from patients with OSCC compared to those taken from healthy individuals and, similarly, in tumoral tissue compared to fibroepithelial polyps [ 82 , 83 ]. A microbial coexistence of C. albicans and a periodontal pathogen P. gingivalis has been described; these two microorganisms have a relationship in which C. albicans shields the P. gingivalis from recognition by the host immune system and, in this way, supports the bacterial infection [ 118 ].…”
Section: Findings and Discussionmentioning
confidence: 99%
“…For example, an increased incidence of the genera Candida , Hannaella , and Giberella was detected in samples of OSCC tumor tissues [ 82 ]. The mycobiota associated with OSCC is summarized in Table 2 [ 82 , 83 , 84 ].…”
Section: Fungi Associated With Oral Cancermentioning
confidence: 99%
“…OSCC is associated with the presence of oral candidiasis, but whether this is a cause rather than a causative relationship is unclear ( 15 , 17 19 , 46 48 ). We previously showed that the diversity of the oral fungal microflora of OSCC patients is remarkably different from that of healthy individuals, with significantly increased fungal burden and diversity in patients with oral tumors.…”
Section: Discussionmentioning
confidence: 99%
“…OSCC is highly associated with the presence of oral candidiasis. However, the details of the cause versus causative relationship are not understood [25][26][27][28][29][30][31] . Our previous study showed that the diversity of the oral fungal microflora of OSCC patients is remarkably different from healthy individuals: the fungal burden and diversity of yeasts was significantly higher in patients with oral tumors compared to the oral cavity of healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies demonstrated a link between OSCC and Candida colonisation of the mouth 23,[28][29][30][31] . Candida infection in patients with cancer is usually considered to be the consequence of an altered immune status because both myelosuppression and mucositis enable the development of oral candidiasis 7,8,32,33 .…”
Section: Introductionmentioning
confidence: 99%